2019
DOI: 10.1080/21645515.2019.1565267
|View full text |Cite
|
Sign up to set email alerts
|

Addressing HPV vaccine myths: practical information for healthcare providers

Abstract: Human papillomavirus (HPV) vaccine uptake consistently lags behind that of other adolescent vaccines. In 2017, uptake of a single HPV vaccine dose and HPV vaccine series completion was 66% and 49%, respectively, compared to uptake of tetanus, diphtheria, and acellular pertussis vaccine (89%) and quadrivalent meningococcal conjugate vaccine (85%). Reasons for not vaccinating adolescents again HPV are varied, and in many cases, are rooted in commonly spread myths and misperceptions about the vaccine. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 134 publications
(160 reference statements)
1
48
1
2
Order By: Relevance
“…Specifically, African Americans, who have higher rates on underlying chronic conditions, are more likely to be hospitalized and die from COVID-19 compared to non-Hispanic Whites [12,21]. A consequence of structural racism and the burdens of social, economic, and environmental injustices have further contributed to widening disparities [4]. For example, African Americans represent a higher percentage of front-line workers that increase virus exposure risk while having lower access to quality healthcare [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, African Americans, who have higher rates on underlying chronic conditions, are more likely to be hospitalized and die from COVID-19 compared to non-Hispanic Whites [12,21]. A consequence of structural racism and the burdens of social, economic, and environmental injustices have further contributed to widening disparities [4]. For example, African Americans represent a higher percentage of front-line workers that increase virus exposure risk while having lower access to quality healthcare [21].…”
Section: Discussionmentioning
confidence: 99%
“…HPV vaccination is more effective when administered to younger adolescents and may be especially beneficial for populations who experience a disproportionate disease burden. Delayed vaccination may also be due to parents associating HPV vaccination with adolescent sexual activity, even though they acknowledge the importance of protecting children from HPV-related infection [4]. Delayed vaccination may lead to missed opportunities for cancer prevention.…”
Section: Vaccine Acceptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…One study found 5 major false beliefs parents hold about HPV vaccine 9 vaccinate. There is some evidence that if clinicians actively engage with parents about these concerns and address them head on, same-day vaccination rates can improve.…”
Section: Address Parental Concerns Including These 5 False Beliefsmentioning
confidence: 99%
“…One paper reports on a systematic review of literature on the determinants of vaccine hesitancy in Europe, 34 and another offers practical guidance to HCPs in how to refute HPV vaccine myths. 35 Meanwhile, a commentary summarizes consensus messages to strengthen parental confidence in HPV vaccination that were generated at the U.S. National HPV Vaccination Roundtable meetings. 36 Other papers address provider, parent, and patient issues specific to understudied countries, such as China, India, and Italy, as well as areas of vaccine hesitancy and/or low vaccination uptake in the U.S. and Canada.…”
Section: Hpv Vaccination Policymentioning
confidence: 99%